DIGITAL AND ARTS BASED TEACHING STRATEGIES IN HIGHER EDUCATION: IMPACT ON CREATIVITY, ENGAGEMENT, ACADEMIC PERFORMANCE - Ponnuchamy, Raja Govindan; AR. Saravanakumar; Muthukrishnan, Nagarajan; Mariappan, Suganthi; Iyer, Lenin (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The changing nature of higher education requires new teaching methods that enhance creativity, interest, and better grades. This paper explores the usefulness of arts-based teaching methods to improve the learning outcomes of learners in higher education institutions. Arts-based pedagogy incorporates visual arts, performing arts, storytelling and digital creative tools into the instructional practices and encourages experiential and student-based learning. The study takes a quantitative study where a structured questionnaire was used to administer the study to undergraduate and postgraduate students of various disciplines. The analysis of data is performed with the help of Structural Equation Modeling (SEM) to study the connections between arts-based teaching techniques, creativity, student engagement, and academic achievement. The results indicate that arts-based instructional methods can influence creativity and student engagement in a positive way with engagement proving as the best predictor of academic outcomes. Also, the research proves the existence of partial mediation, whereby creativity and engagement are the major processes in which arts-based pedagogy affects academic performance. Compared and contrasted analysis reveals that arts-based integrated strategies are more effective in promoting active engagement, cognitive and critical thinking, and conceptual knowledge compared to conventional lecture style-based techniques of instruction. The research makes a contribution to the current body of literature by suggesting and empirically justifying an all-inclusive conceptual framework in relating pedagogical innovation with cognitive and affective learning outcomes. In a practical way, the results indicate that institutions of higher learning should implement the use of interactive and experiential teaching methods to improve student learning experiences. Some limitations of the study, such as the cross-sectional nature and a discipline-specific sampling, do not deny it any useful information to educators, policymakers, and curriculum designers. Further studies can study the longitudinal effects and incorporation of new technologies like virtual and augmented reality in arts-based learning.